The Russian Far East : strategic development of the workforce - Novikova, I. V. (Irina Viktorovna) (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press Inc. ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This monograph The Russian Far East: Strategic Development of the Workforce by Irina V. Novikova presents an integrated concept of the workforce development strategy for the Far Eastern Federal District (FEFD) of Russia. This concept is based on the strategizing methodology developed by Vladimir L. Kvint. The concept takes into account contemporary global, national, and regional development trends in workforce, employment, and labor market issues, including the active influence of information and communication technologies (ICT) and the appearance of numerous novel forms of employment. The conclusions and proposals in this work are built on the analysis of a wide range of analytical data. Workforce development programs, from the Tsarist era until the present, are analyzed in this work. Here, creative approaches to the workforce provision problems of the Russian Far East and appraisal criteria for the strategy's public and economic efficiency are proposed. This work is of interest to a wide range of experts, researchers, and employees of government agencies who are concerned with the issues of strategic workforce development in the Russian Far Eastern Federal District. In addition, this study will benefit those who reside in the region, and those who intend to relocate to, reside, and work in the area of the Russian Far East. This book belongs to the Strategy of the Russian Far East Library developed under the editorial supervision of Sergey Darkin and Vladimir Kvint."--
Analysis of Key Practices for the Development of the Russian Far East's Labor Resources -- Trends in Development of the Far Eastern Federal District's Workforce -- Priorities to Increase the Workforce in the Russian Far East -- Key Elements of the "Strategy of Workforce Development in the Far Eastern Federal District Until 2035".
OCLC-licensed vendor bibliographic record.
Keywords: Labor supply -- Russia (Federation) -- Russian Far East; Labor market -- Russia (Federation) -- Russian Far East; Manpower policy -- Russia (Federation) -- Russian Far East; SCIENCE / Life Sciences / General